Investigando o grande mundo das pequenas partículas: uma proposta para ensinar física de partículas no ensino médio - Oliveira, Larissa de Sousa (2024)
A review of the literature on the challenges of teaching physics in secondary schools revealed that there is great concern about the low contribution of Modern and Contemporary Physics topics to the school curriculum. Given the importance of teaching Modern and Contemporary Physics for students to develop a vision of science as an integral part of society, this study sought to build a didactic proposal that would allow Contemporary Physics topics to be included in secondary education. To this end, the Critical Meaningful Learning Theory was adopted as the theoretical-educational framework, which resulted in the development of a Potentially Meaningful Teaching Units (UEPS) on the subject of particle physics. The Educational Product developed consists of a booklet containing materials for working from the earliest conceptions of the constitution of matter to the development of the Standard Model of Elementary Particles and technologies for detecting subatomic particles. The implementation of the product in a first grade high school class at a public school in Ceará revealed positive results in terms of the knowledge acquired by the students and the protagonism developed by them, easing up their meaningful critical learning. In addition, it was found that, through its application, the Educational Product contributed to students feeling more motivated to study Physics.